2013
DOI: 10.1103/physreva.88.023840
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear waveguiding of few-cycle optical solitons in a planar geometry

Abstract: We consider the guiding of a few-cycle optical soliton by total internal reflexion, in a planar geometry. By means of numerical solution of a cubic generalized Kadomtsev-Petviashvili equation, we show that, for intensities high enough to induce soliton formation, the nonlinear effects considerably widen the guided mode and can even prevent guiding for the shortest pulses and the narrowest waveguides. However, waveguiding can be achieved by means of a steep variation of the nonlinear coefficients, e.g., by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…We considered some time ago [54] the waveguiding problem of few-cycle pulses in the frame of mKdV-type models, and we showed that nonlinear coupling can strongly modify the characteristic waveguiding properties. More recently, we established the generic equations that account for the coupling between two adjacent optical waveguides [55].…”
Section: Introductionmentioning
confidence: 99%
“…We considered some time ago [54] the waveguiding problem of few-cycle pulses in the frame of mKdV-type models, and we showed that nonlinear coupling can strongly modify the characteristic waveguiding properties. More recently, we established the generic equations that account for the coupling between two adjacent optical waveguides [55].…”
Section: Introductionmentioning
confidence: 99%